Le sentiment d'efficacité personnelle des enseignants et leurs pratiques de gestion des comportement en classe - Gaudreau, Nancy; Royer, Égide; Beaumont, Claire; Frenette, Éric (Canadian Journal of Education/Revue canadienne de l'éducation, 2012)
Teachers’ personal efficiency has an important influence on a range of variables that are directly related to student success. Among these, teachers have collaborative educational practices and preferred methods for dealing with poor behavior in the classroom. This article presents a literature review in order to profile the main theoretical models that explain teachers’ personal efficiency and its effects on the experiences of both teachers and students with behavioral difficulties in school. Keywords: Personal efficiency in teaching, behavioral disorders, classroom management